Risk of schizophrenia and bipolar disorder in patients with multiple sclerosis: Record-linkage studies - Meier, U-C; Goldacre, R; Ramagopalan, SV; Goldacre, MJ (Frontiers Media, 2020)
Background: The epidemiology of psychiatric comorbidity in multiple sclerosis (MS) remains poorly understood.